PENGARUH KEPERCAYAAN DAN KUALITAS HUBUNGAN TERHADAP DAYA SAING KOPERASI PERTANIAN: STUDI EMPIRIS DALAM RANTAI PASOK KUD SAE MALANG - Destyana Ellingga Pratiwi; Andrean Eka Hardana (Agripita: Jurnal Agribisnis dan Pembangunan Pertanian, 2017)
In recent years, supply chain has received attention from researchers and business practitioners. There were many studies have been conducted to identify what factor did influence the competitiveness the supply chain. The aim of this study is to investigate the effect of trust and quality of relationship on supply chain of KUD. This research employed structural equation modeling (SEM) as the analyzing method, and used primary data gathered from milk producers/farmers, management staffs of KUD, and retailers that involved in milk chain in Malang Regency. The conceptual model comprises four hypotheses. The results show that those hypotheses are proved, which means that variables of trust, quality of communication, and quality of relationship positively affect the competitiveness of KUD.